Knowledge, attitude and practice among healthcare professionals regarding the use of personal protective equipment at tertiary care hospitals in Peshawar - Adeel, Muhammad; Zareef, Adil; Anas, Muhammad; Ali, Muhammad Armaghan; Ali, Muhammad Aftab; Asim, Mohammad (International Journal of Pathology, 2025)
Background: Personal protective equipment is designed to safeguard healthcare workers and patients from potential risks during healthcare activities. The proper utilization of PPE serves as a crucial strategy for mitigating the transmission of infections within healthcare settings, thereby minimizing the risk of both healthcare-associated infections and community spread. In this study we tried to explore and assess the knowledge, attitude and practice of healthcare professionals regarding use of Personal protective equipment (PPE).Methods: A cross-sectional study was conducted at Northwest General Hospital (a private sector tertiary healthcare hospital) and Hayatabad Medical Complex (a public sector tertiary care hospital) from March to August 2023. Data was collected from 260 healthcare workers i.e. Doctors and Nurses from both institutions through a preformed questionnaire containing a total of 27 questions.Results: There was a slight positive correlation between increasing years of practice and knowledge regarding PPE (Pearson correlation = 0.017). There was a slight positive correlation between increasing years of practice and attitude (Pearson correlation = 0.035). There was a positive correlation between increasing years of practice and practice of PPE (Pearson correlation=0.147), and there was also a significant association (0.018) between increasing years of practice and practice of PPEConclusion: Study shows that the healthcare professionals have good knowledge and attitude regarding use of PPE, but there are still gaps in practicing PPE.